Impact of E-Government Technologies on Citizen Engagement and Service Delivery: A Case Study of Local Government Units in Caloocan - Valle, Janet S.; Bugayao, Zelve Rose; Gutierrez, Cristofer; Malang, Bernandino P.; Malang, Jocelyn DS. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The emergence of technology significantly affects the transformation of how the local government and its citizens interact through the utilization of the e-government services platform. This study focuses on the impact of e-government technologies on citizen engagement and service delivery in the Local Government Unit (LGU) of Caloocan City. The results high-light citizens' perspectives on Caloocan's e-government platform, under-scoring concerns, challenges, and suggestions for improvement. Privacy and security rank highly among citizens’ concerns, while language acces-sibility is less of an issue. However, survey data from 250 respondents highlight that 73% expressed satisfaction with the user interface and design of the e-government platform, while 58% trusted the platform's security and privacy measures, though 10% indicated a lack of trust in the system’s data security. To build on this foundation, respondents sug-gest improvements such as better customer support, clearer communica-tion, and training opportunities that could help boost confidence and en-courage active participation. By means of addressing these areas, the platform could be more effectively support the community’s needs, en-hancing trust and fostering a stronger connection between citizens and the local government.